PELEPASAN HAK ATAS UPAH DALAM PERJANJIAN BERSAMA ANTARA PENGUSAHA DAN PEKERJA/BURUH - Elizabeth Irianti Mayangsari Runtu (Jurnal HUKUM BISNIS, 2019)
Humans must work to maintain their survival, without working humans will not be able to maintain their lives well. Economic development is inseparable from the name of employment which covers all aspects of people's lives where labor and employers conduct a work relationship as an effort to meet the economic needs of the community. Work agreements between employers and workers cannot be separated from the discussion of the problem of the amount of wages and the method of payment. In accordance with Law No. 13 of 2003 concerning Manpower Article 88 paragraph (1), paragraph (2) and paragraph (3a), the government establishes wage policies to protect workers in order to obtain income that fulfills decent livelihoods for humanity, including through minimum wages. In this thesis the constituent focuses on releasing the right to wages made by workers / laborers with a joint agreement between the parties, which also discusses sanctions imposed on employers if the employer pays a wage under the minimum wage stipulated by the local governor. And the compilation target in this journal is whether the release of rights in a collective agreement has binding power in the implementation of Constitutional Court No 72 / PUU-XIII / 2015 decision, of course in legal corridors as stipulated in Law Number 13 of 2003 concerning Labor. Hopefully this journal can be a useful reading and add insight to its readers.